User Behavior Assessment of Household Electric Usage - Mulyono, Nur Budi (The Asian Journal of Technology Management (AJTM), 2013)
Abstract. Energy resilience is one of the famous issues among researchers and practitioners in energy sector. With enabling new technologies in power engineering for smart grid such as distributed generation, distributed storage, and intelligent information and management, each household community can establish a resilience energy production, distribution, and consumption. A household in smart grid system behaves as a customer and producer at the same time. This condition enabled them to reduce the power shortage in the peak hours, reduce CO2 pollution using renewable electricity, and minimizing electricity usage by changing life style. In developing countries, the amount of electricity supply is less than its demand. Most of the demand comes from the household that has peak load on nighttime. Keywords: User behavior, Game theory, Smart grid, Heating and cooling appliances, Energy resilientdoi:10.12695/ajtm.2013.6.2.1 How to cite this article:Mulyono, N. B. (2013). User Behavior Assessment of Household Electric Usage. The Asian Journal of Technology Management 6 (2): 65-71. Print ISSN: 1978-6956; Online ISSN: 2089-791X. doi:10.12695/ajtm.2013.6.2.1